Comparative analysis of the gut microbiota composition and diversity in Erinaceus amurensis from the Wandashan Mountain range area based on metagenomics - Jia, Xiuqi; Li, Qiang; Yang, Xinyu; Li, Dianwei; Jin, Zhimin (Frontiers in Microbiology, 2024)
This study aimed to preliminarily explore the composition and diversity of intestinal bacteria in Erinaceus amurensis during breeding period, aiding in the field rescue and population conservation efforts of Erinaceus amurensis. This also provides foundational data for further research on the prevention and screening of Emerging Zoonotic Infectious Diseases and the experimental animalization of wild Erinaceus amurensis. Between April and July 2023, we collected 13 fresh fecal samples from Erinaceus amurensis at the Sishan Forest Farm in Jidong County, Heilongjiang Province, situated within the Wandashan Mountain range. Utilizing metagenomic sequencing technology, we conducted a comparative analysis of the gut microbiota composition and diversity in wild Erinaceus amurensis across different genders and between adult and fetal individuals within the same habitat. Our results revealed significant differences (P < 0.01) in the classification and diversity of gut microbiota between genders and between adult and fetal Erinaceus amurensis. Specifically, the dominant bacterial groups in the gut of Erinaceus amurensis were Pseudomonas, Proteobacteria, and Enterobacteriaceae. In male and female Erinaceus amurensis, the dominant bacterial groups were Pseudomonas, Bacteroides, and Firmicutes, with variations in bacterial abundance and diversity. While male and female Erinaceus amurensis exhibited similar microbial compositions, they displayed significant differences in specific bacterial classifications. The dominant bacterial group in fetal Erinaceus amurensis was Proteobacteria, which demonstrated lower diversity and abundance compared to the adult group. Furthermore, the types and abundance of pathogenic or opportunistic pathogens in the gut of fetal Erinaceus amurensis and male Erinaceus amurensis were higher than those in female Erinaceus amurensis. The analysis of experimental results indicates that Erinaceus amurensis in this region either have or are at risk of developing inflammation related to the intestinal and urinary tracts, as well as skin-related issues. Consequently, it is advised that forestry and wildlife conservation personnel in this area prioritize treatment against these specific pathogens when conducting rescue operations for Erinaceus amurensis in the wild.